Lesiones de rodilla en deportistas: período de desentrenamiento (2021)
Knee injuries are common in athletes and recurrence after the first injury also occurs in most cases. Therefore, the number of studies on this topic is increasing, but there are few studies that relate the subject and its consequences to the detraining period, although this period can bring great losses. In order to identify these risk factors, a bibliographic review was carried out in the databases PubMed and the Coordination for the Improvement of Higher Level Personnel, using the PICOT search strategy. Of the 354 articles identified, 12 met the criteria and were analyzed in their entirety, considering the hypothesis of a correlation between knee injuries and detraining. From this, it was concluded that it is necessary to develop a protocol for extended detraining to prevent withdrawal syndrome and promote the health maintenance in athletes, especially those who have suffered knee injuries. Finally, further research on the subject is suggested to confirm the correlation.